Patient, prisoner or person? - Small Dan (BMC, 2006)
Abstract Case studies provide rich descriptions of significant vignettes that highlight atypical systemic or clinical problems and identify potentially important research questions. The case study presented by Venters, Razvi, Tobia and Drucker (2006) describes an unfortunate set of events pertaining to an individual's experience as they were failed by s several systems all at once and neglected for having had experience with an addiction. This commentary provides some remarks on the case study with respect to differing institutional narratives as they pertain to lived experience in the context of everyday life. It is suggested that, in the special case of addiction, the mistreatment of the subject of the case study, Mr. Ortiz, is not an exception to the norm, but the norm itself for people living with addictions and their families.